Learning Soccer in Elementary School: Using Teaching Games for Understanding and Digital Media - Greve, Steffen; Diekhoff, Henrike; Süßenbach, Jessica (Frontiers in Education, 2022)
In this study, a digitally supported teaching process for elementary school was investigated using TGfU. The investigation was carried out to investigate the research question: How do elementary school students experience and interpret the use of digital media when teaching soccer using the TGfU approach in PE lessons? To this end, a teaching unit on soccer was carried out in fourth grade four classes according to the TGfU teaching method. During the unit, the students recorded each other with an app and tagged certain game situations according to predefined criteria. The sequences (approximately 8 seconds) were discussed together during the reflection phases. Following the lesson, 65 guided interviews were conducted with students. Data collection and analysis were based on grounded theory methodology. The interviews revealed very ambivalent perspectives on the use of the app. Overall, the students were very reflective about the use of the app. The digital medium was interpreted as an aid in the learning process and was clearly less important than playing the game itself. The children reported many attempts to implement the tactical ideas discussed together in the reflection phases in the subsequent game. However, many students who described themselves as good soccer players saw the app’s use as rather superfluous. The misuse of the film option was also interesting: The students often used this option as a video assistance referee, for example, to quickly clarify disputed situations. The results thus show an extremely pragmatic handling of the digital tool by the students.